Tropical dermatology: Venomous arthropods and human skin Part II. Diplopoda, Chilopoda, and Arachnida - Haddad, Vidal [UNESP]; Costa Cardoso, Joao Luiz; Lupi, Omar; Tyring, Stephen K. (Mosby-elsevier, 2012)
Members of arthropod classes Chilopoda (centipedes), Diplopoda (millipedes), and Arachnida (spiders and scorpions) cause tissue injury via bites, stings, and/or a release of toxins. A few members of the Acari subclass of Arachnida (mites and ticks) can transmit a variety of infectious diseases, but this review will cover the noninfectious manifestations of these vectors. Dermatologists should be familiar with the injuries caused by these arthropods in order to initiate proper treatment and recommend effective preventative measures. (J Am Acad Dermatol 2012;67:347.e1-9.)
Keywords: bite; centipede; envenomation; millipede; mite; scorpion; spider; sting; tick; tropical dermatology